Car PC hacks - Stolarz, Damien (O'Reilly Media, 2005)
A car PC or carputer is a car tricked-out with electronics for playing radio, music and DVD movies, connecting to the Internet, navigating and tracking with satellite, taking photos, and any electronic gadget a person wants in a car. All these devices are managed and controlled through a single screen or interface. The only place car PC enthusiasts can go for advice, tips and tools is a handful of hard-to-find Web sites--until now. Car PC Hacks is your guide into the car PC revolution. Packing MP3 players, handheld devices, computers and video-on-demand systems gives you a pile too heavy to carry. But add a car and put them together, you've got a powerful and mobile multimedia center requiring no lifting. The next time you give kids a lift, you won't hear, "Are we there yet?" Instead, expect "We're there already?" as they won't want to leave the car while playing video games from multiple consoles. Car PC Hacks is the first book available to introduce and entrench you into this hot new market. You can count on the book because it hails from O'Reilly, a trusted resource for technical books. Expect innovation, useful tools, and fun experiments that you've come to expect from O'Reilly's Hacks Series. Maybe you've hacked computers and gadgets, and now you're ready to take it to your car. If hacking is new and you would like to mix cars and computers, this book gets you started with its introduction to the basics of car electrical systems. Even when you're unclear on the difference between amps and watts, expect a clear explanation along with real-life examples to get on track. Whether you're venturing into car PC for the first time or an experienced hobbyist, hop in the book for a joy ride.